2008
DOI: 10.1111/j.1468-3083.2008.02698.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of facial skin attributes on the perceived age of Caucasian women

Abstract: Different skin attributes influence the estimation of age. These attributes have a different weight in the evaluation of the perceived age, depending on the age and of the observer. The most important attributes to estimate age are eyes, lips and skin colour uniformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
2
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(159 citation statements)
references
References 35 publications
7
140
2
7
Order By: Relevance
“…Consistent with most of researches on voices, no difference between male and female participants was reported in age estimation from faces (Dehon & Brédart, 2001;Voelkle et al, 2012). Moreover, as for voices, when a gender difference was reported, females estimated the age more accurately than males (Nkengne et al, 2008;Vestlund et al, 2009). Similarly, Vestlund et al (2009) found that females are less biased than males and more accurate but only with faces from 56 to 65 years.…”
Section: Gender Of Participantssupporting
confidence: 71%
See 2 more Smart Citations
“…Consistent with most of researches on voices, no difference between male and female participants was reported in age estimation from faces (Dehon & Brédart, 2001;Voelkle et al, 2012). Moreover, as for voices, when a gender difference was reported, females estimated the age more accurately than males (Nkengne et al, 2008;Vestlund et al, 2009). Similarly, Vestlund et al (2009) found that females are less biased than males and more accurate but only with faces from 56 to 65 years.…”
Section: Gender Of Participantssupporting
confidence: 71%
“…Similarly, Vestlund et al (2009) found that females are less biased than males and more accurate but only with faces from 56 to 65 years. Nkengne et al (2008) also provided some support for a better performance in women. However, only females' faces were used in this study.…”
Section: Gender Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also provided some empirical support for better age estimation performance and less bias among women (Nkengne et al, 2008;Vestlund et al, 2009). Although the reasons for this increased age estimation bias in the male group are unclear, this may be partly because women tend to be more appearance-conscious and more sensitive to their age; it could also be because women tend to observe others and/or themselves in the mirror more frequently than men during the common practice of applying cosmetics.…”
Section: Discussionmentioning
confidence: 90%
“…Perceived age is a specifi c term referring to facial appearance and comprising multiple facial features such as the nasolabial fold, skin wrinkling, the presence of pigmented spots or lip height (2,3).…”
Section: Introductionmentioning
confidence: 99%